Issues of Data Management in the Library: A Case Study - Zangana, Hewa Majeed (International Journal of Computer Sciences and Engineering, 2019)
This study reviews the problems of data management in the Library of International Islamic University Malaysia (IIUM), in order to identify, to what extent such problems have affected the smooth running and operations of the library, and to successfully address and solve these problems. inside IIUM library, we observed that, they engage in standard library operations such as lending, borrowing and also operating as a repository to the university community, where documents, books, journals and other reading materials of the IIUM university are being kept as a valid reference to the public & members of IIUM, such as IIUM students, staff, as well as students of other universities in Malaysia and abroad, researchers, academicians and other interested parties. All the related data being used by the library for such activities must be consistent, relevant and reusable by all stakeholders of the IIUM community, which would have to play a significant role in ensuring adequate data management. However, there were several efforts on tools of measurement or techniques of keeping and maintaining a data with the right features, but unfortunately, such efforts still need to be evaluated due to the continuous changes and occurrence of these problems of data management nature.